HISTORY EDUCATION AS A FOUNDATION FOR THE CRITICAL THINKING OF ELEMENTARY SCHOOL STUDENTS - Tazkiyah, Era (Universitas Muhammadiyah Ponorogo, 2024)
History education is not only concerned with the aspect of the time dimension but there are other things that can be taken from the value of history. This research is descriptive qualitative research using a combination of literature study methods and historical methods. The combined research model of James Schreiber and Kimberly Asner-Self regarding literature review studies with Kuntowijoyo's model of historical research studies. The researcher used steps from historical studies and a literature review to make this research seen from a more contemporary angle. Data analysis uses the historical method by criticizing the sources that will be used in writing. The research instrument in this paper is the researcher who collects the main focus and collects sources. The purpose of this study is to analyze and describe the important role of history education that can help become the foundation of students' critical thinking skills at the primary school level in Indonesia. The results of this study explain that history education needs to be given to students at the primary school level. Primary school students can be said to have the ability to interpret, analyze, evaluate, infer, and explain an event, especially in simple history education. The development of critical thinking skills in history education can be done by improving the good narrative skills of history teachers by inviting students to dive into the past. Teachers can visit places that have high historical heritage value and provide factual explanations in the context of the present. History education can help elementary school students understand an event that is not only about time but also important as a foundation for students' critical thinking to recognize events as a whole and be able to understand situations and information related to the environment around students.